PREDIKSI KERAWANAN BANJIR LAHAN SAWAH BERBASIS CURAH HUJAN AKTUAL DAN KERENTANAN PANGAN DI WILAYAH SUB DAS BILA PROVINSI SULAWESI SELATAN - Abdullah Abdullah; Risna Hardianty Haedar; Annas Boceng (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
Bila Watershed (DAS) is the water source provider at the agricultural activities in several districts in South Sulawesi: Enrekang (upstream), Sidenrang Rappang (middle) and Wajo (downstream). For last five years, every years there are floods, Sidrap and Wajo districts, and affect the level of food security. This study aims to predict the pattern of changes in rainfall and flood events for the next 10 years. Predictions of rainfall patterns and flood events are used as the basic for mapping the level of flood vulnerability of paddy fields and food vulnerability.Climate change analysis uses the Global Change model (GCM) with a short-term (10 years) baseline average monthly rainfall simulation. Precipitation data for the last 10 years from the nearest climate station and land biophysics (slope, soil physical (permeability), drainage density, land use). The data were analyzed spatially to obtain class data for each parameter and validated through a field survey. The data for each parameter is overlaid with data and maps using a geographic information system (ArcGIS) application. The results of the overlay map form the projection of flood susceptibility and food vulnerability in the Bila watershed area. The results of the analysis show that the monthly rainfall volume >300 mm/month occurs in April - July and rainfall <200 mm occurs in August - March. The level of flood vulnerability in the high and very high categories is 31.28% (53,252.09 ha). The potential for flood vulnerability of paddy fields is high to very high, 96.71% (38,069.06 ha) of the total paddy fields in the Bila watershed area (39,363.55 ha).Enrekang distric has a very high level of food security with a ratio demand is 414 kg/capita/ year with paddy producton is 9,108,99 tons/year, compared to Sidrap and Wajo districts with a low level of food security